The link between structural connectivity and neurocognition illustrated by focal epilepsy. Issue 2 (1st June 2018) - Roger, Elise; Petit, Laurent; Perrone‐Bertolotti, Marcela; Job, Anne‐Sophie; Minotti, Lorella; Kahane, Philippe; Baciu, Monica
ABSTRACT: Increasing attention is being paid to the assessment of white matter properties and its structural connectivity, both in healthy subjects and patients with cerebral lesions. Within this framework, new neurocognitive models based on hodological properties have been developed under a connectomic perspective in order to explain substrates and cognitive mechanisms related to cerebral functions such as language and memory. With regards to focal and drug‐resistant epilepsy conceived as a network disorder, new insights in terms of structural connectivity have led to significant advances in epilepsy research, concerning fundamental research (neurocognitive mechanisms of plasticity) and clinical application (optimization of decision making for curative surgery). We believe that such findings in the literature, focused on the role of white matter in cerebral functioning in relation to neurocognition, may be helpful for both researchers and clinicians working in the field of epilepsy.